Reduction of sixth‐order radial force by harmonic current control and its application to EPS motors. Issue 3 (11th September 2019) - Watahiki, Masanori; Mori, Tomonari; Lan, Linfeng; Tanaka, Junya; Ueda, Tomoya; Fukumura, Tomohiro; Kanematsu, Masato; Fujimoto, Hiroshi
Abstract: To improve noise and vibration of Electric Power Steering (EPS) system, we focus on the reduction of the sixth‐order radial force of an EPS motor by regulating its harmonic current. Because an EPS system is operated in a wide speed range, a reduction method is required to work even for dynamic motor speed. In this article, we introduce our method and report its test result to show the reduction of sixth‐order radial vibration of an EPS motor.